ASSESSING THE PERFORMANCE OF TROPICAL FOREST SEEDS ENCAPSULATED WITH GELS FROM VITIS VINIFERA AND SODIUM ALGINATE FOR DIRECT SEEDING - Dutra, F. B.; de Almeida, L. S.; Dona, D. B.J.; Piotrowski, I.; da Silva, J. M.S.; Sabonaro, D. Z.; dos Santos, V.; Chaud, M. V.; da Silva, A. M. [UNESP]; Piña-Rodrigues, F. C.M. (Forest Research Institute Malaysia, 2023)
The objective of the study was to evaluate the encapsulation of seeds of tropical forest species with cellulose gel (CG) from Vitis vinifera and sodium alginate, with and without biostimulant, in order to optimise its size, shape and performance for direct seeding. Four species used in direct seeding were selected, i.e., Bixa orellana L., Mimosa bimucronata (DC.) Kuntze, Trema micrantha (L.) Blume and Psidium guajava L.. The experimental design was completely randomised with eight treatments and four repetitions of 100 seeds each. Encapsulation affected the physical quality of the seeds, however, it facilitated their handling and visualisation in germination tests, especially for T. micrantha, with a 4-fold increase in size with alginate gel and 2-fold with CG. Sodium alginate performed better than CG, synchronising the growth of B. orellana seedlings. The biostimulant showed potential to synchronise germination, vigor and seedling growth when associated with dormancy break for M. bimucronata, and promoted seedling growth for P. guajava. Sodium alginate gel has potential for seed enhancement, while CG encapsulation needs to be improved in relation to its physical characteristics, requiring further studies. The biostimulant can be recommended for enhancing uniformity of seed emergence in direct seeding.
Keywords: coating; germination; seed enhancement; Seedling establishment; small seeds